FUZZY LOGIC MENENTUKAN GURU TERBAIK MENGGUNAKAN METODE SUGENO DI BATAM SMK PUTRA JAYA SCHOOL - Panjaitan, Samuel; Fajrin, Alfannisa Annurrullah (LPPM Universitas Putera Batam, 2021)
Teachers are teaching staff who educate and provide knowledge to students. Teachers must be able to protect without favoritism. Without the role of a good teacher, students may be easily influenced by bad things, therefore teachers must have quality human resources in order to provide teaching to students. Based on this background, the authors conducted research to determine the best teacher using the Sugeno method in one of the private schools in Batam, namely SMK Putra Jaya School. Assessments carried out include Understanding School Policies, Mastery of Materials, Discipline, and Educating Attitudes. With fuzzy logic the value obtained has a membership value between 0 and 1. For data processing using MATLAB. The first step is the completion of the best teacher assessment using the Sugeno method, namely by determining the input variables and output variables which are firm sets, the second step is to change the input variables into fuzzy sets with a fuzzification process. From the results of manual calculations and data testing in Matlab, the best results with the test are 1. Thus, Sugeno's fuzzy logic can be used to determine the best teacher at SMK Putra Jaya School.